Czy Saul Kripke mógłby być fenomenologiem? - Grabarczyk, Paweł (Filozofia Nauki, 2003)
In this article I am trying to compare the methods of phenomenology and analytic philosophy. Such a general comparison is of course impossible in a small article. In order to make it possible I am comparing selected authors. Phenomenology is thus represented by Husserl and Ingarden, analytic philosophy by Putnam and Kripke (they are chosen because of their realism and essentialism). I am trying to analyze the way the authors describe their methods. First I am analyzing analytic philosophy from the phenomeneological point of view, then phenomenology from the point of view of analytic philosopher. I'm. pointing out that Kripke and Putnam often say about intuition, and that they do not understand it as any kind of linguistic intuition. Then I'm. pointing out that phenomenologists often refer to the way w describe things, although they are convinced that their experience is always prior to any linguistic form. I am suggesting that even if we agree that the practice of both schools is similar, and that the description of methods could be translated, there is no chance of a real agreement between phenomenology and analytic philosophy. My thesis is that neither the practice nor the description of the way we obtain our philosophical goals is important. What really is important is all the philosophical background (ontology, philosophical assumptions and the like). In this particular situation considered in my article, the most important factor is the answer for the following question: Can we think without the language? Phenomenologist can not answer 'no' to this question. If he did he would admit that his philosophy isn't free of assumptions. Analytic philosopher can not answer 'yes' to this question. If he did he would admit that he is interested only in some kind of 'package for thought'. The answer itself depends on some kind of philosophical faith. Thus, the answer for the main question of my article depends only on Kripke's will of changing his declaration of faith.